Moderasi Beragama dalam Al-Qur’an sebagai Tuntunan untuk Menciptakan Kesejahteraan dalam Kehidupan Berbangsa dan Bernegara - Syarifudin Zaidan, Akmal; Ahmad Mansur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesia is a country that has a diversity of ethnicities, races, and religions. Diversity in any field will indeed lead to differences, and it must be known that these differences will certainly trigger potential conflicts. If conflict is not managed properly, it can lead to extreme attitudes in maintaining different interpretations of each group's truth claims. So to create a prosperous and harmonious national and state life, it is necessary to have moderation in religion as a form of effort for welfare and harmony between religious communities. Al-Qur'an as a moderated guide and guide to determine a new direction for the general public in understanding religion and bring changes to a more balanced perspective.